DIKOTOMI KEKUATAN PEMBUKTIAN LEGALISASI DAN WAARMERKING: FORMALITAS ADMINISTRATIF ATAU INSTRUMEN KEPASTIAN HUKUM? - Nyoman Ayu Fitri Noviani; Ni Putu Rai Yuliartini; Rimah Afsari (Kampus Akademik Publiser, 2026)
Legalization and waarmerking are notarial authorities concerning private deeds that are often perceived in practice as having the same legal consequences. This misconception has led to the assumption that any document legalized or registered by a notary automatically possesses the same evidentiary value as an authentic deed. This study aims to analyze the differences in the functions and legal consequences of legalization and waarmerking, as well as to examine both notarial acts from the perspective of the theory of legal certainty in order to determine whether they merely constitute administrative formalities or function as instruments of legal certainty. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials were collected through library research, including legislation, legal literature, and relevant scholarly journals, and were analyzed using a descriptive qualitative method. The findings indicate that legalization provides stronger evidentiary value because the notary verifies the identity of the parties and authenticates their signatures, thereby providing preventive legal protection. In contrast, waarmerking does not involve verification of the parties' identities or signatures but only establishes certainty regarding the existence of a document on the date it is registered. Therefore, legalization serves as a substantive instrument of legal certainty, whereas waarmerking primarily functions as an administrative formality while still providing limited legal protection by establishing certainty of date and safeguarding the interests of third parties.